2019
DOI: 10.3857/roj.2018.00577
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors, failure patterns and survival analysis in patients with resectable oral squamous cell carcinoma of the tongue

Abstract: Purpose There is sparse literature on treatment outcomes research on resectable oral tongue squamous cell carcinoma (OTSCC). The aim of this study was to measure the treatment outcomes, explore the failure patterns, and identify the potential clinicopathological prognostic factors affecting treatment outcomes for resectable OTSCC. Materials and Methods It is a retrospective analysis of 202 patients with resectable OTSCC who underwent upfront primary surgical resection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…There were 26 studies originated from Asian countries (China, India, Korea, Japan, and Pakistan), and the remaining ten studies were from non-Asian countries (USA, Europe, Australia, Italy and Brazil). Among them, ten studies included oral tongue SCC [14][15][16][17][18][19][20][21][22][23][24] , and the other two studies were focused on floor of mouth cancer 7 and buccal mucosa SCC 25 , respectively. The tumor site of OSCC was mixed in the other 24 studies .…”
Section: Study Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 26 studies originated from Asian countries (China, India, Korea, Japan, and Pakistan), and the remaining ten studies were from non-Asian countries (USA, Europe, Australia, Italy and Brazil). Among them, ten studies included oral tongue SCC [14][15][16][17][18][19][20][21][22][23][24] , and the other two studies were focused on floor of mouth cancer 7 and buccal mucosa SCC 25 , respectively. The tumor site of OSCC was mixed in the other 24 studies .…”
Section: Study Characteristics Of Included Studiesmentioning
confidence: 99%
“…OS, DSS, DFS were the identified endpoints. Among them, 11 studies including 12783 patients reported the OS 7,17,20,22,26,30,31,37,38,41,46 (Figure 3A), seven studies involving 3470 patients reported the DSS 24, 32, 37-39, 46, 47 (Figure 3B), and the other three researches with 731 follow-ups reported the DFS 25,30,43 ( Figure 3C). Among studies focused on OS, Wei study (2019) 46 from Group DSS was excluded on account of overlapping with the patient pool of Chen study (2014) 31 .…”
Section: Prognostic Value Of LVI In Osccmentioning
confidence: 99%
“…However, the inaccuracy of clinical examination and imaging to reliably detect occult cervical lymph node micrometastasis has resulted in elective neck dissections becoming a standard of care for a vast majority of the OTSCC management, based on the evidences from randomised controlled trials 9 . The other clinicopathological factors predicting poor prognosis include increased depth of invasion 10 , 11 , increasing pT, the presence of extra-capsular extension 12 , 13 and endophytic appearance of tumor 14 . In spite of the multiple attempts made to classify molecular markers in OTSCC with promising candidates emerging 15 19 , they have not been translated to clinics and therapeutic decisions are still largely driven by the classical clinico-pathological factors like tumor stage, patient’s age and performance status 20 which may be insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…other clinicopathological factors predicting poor prognosis include increased depth of invasion 10,11 , increasing pT, the presence of extra-capsular extension 12,13 and endophytic appearance of tumor 14 . In spite of the multiple attempts made to classify molecular markers in OTSCC with promising candidates emerging [15][16][17][18][19] , they have not been translated to clinics and therapeutic decisions are still largely driven by the classical clinico-pathological factors like tumor stage, patient's age and performance status 20 which may be insufficient.…”
mentioning
confidence: 99%
“…Unfortunately, the clinical outcomes of patients with TSCC remain unsatisfying and are mainly attributed to rapid tumor progression. 4 Despite numerous scientific studies of basic cellular activity in TSCC, [5][6][7] the detailed molecular events involved in TSCC carcinogenesis and progression are largely elusive. Therefore, a complete recognition of the mechanisms underlying TSCC pathogenesis is urgently needed, as this may be useful in the identification of potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%